Comparison of Various Gradient Types for Biological Image with Morphological Operations - Hussein , Layla; Abbas , Amel H. (Iraqi Journal of Science, 2022)
Biological image edge detection preserving the important structural properties in an image. Detecting accurate edges are very important for analyzing the basic properties associated with a biological image. Gradient operator plays very important role in edge detection. In this paper the images had been using are color biological images taken from microbiology laboratory at the biological department college of science Al-MustansiriyhUniversity and the effect of gradient operation have applied on around 10 different biological color images but view only two. In our proposed approach comparative of various gradient of biological image include (gradient of image, gradient of image using first order derivative edge detection (Soble,Prewitt,Roberts)and gradient image using morphological operation and The comparative output images using quality assessment include (MSR, PNSR, l2rat, maxerr, entropy). The software tool that has been used is MATLAB 7.0 from the results we found that morphological and Robert gradient edge detection algorithm better performs than the others and are important with extraction features of biologic images.